When does infrastructure function well? A multi-actor performance criteria typology. (18th September 2006) - Van De Riet, Odette A.W.T.; Turk, Adam
Infrastructures are of vital importance to society. Infrastructures boost economic growth and quality of life by increasing communication, and travel and transport possibilities, bringing comfort to our homes, etc. But infrastructures can also have negative effects. For example, they can harm the environment and exhaust scarce resources. We are only beginning to understand the effects of an infrastructure policy. Many infrastructure policies have yielded favourable results, but some have clearly worked better than others. As policymakers seek to improve the infrastructure system, it is important that they understand the trade-offs that different policies entail. Thus, they need to have a good understanding of the different functions infrastructure fulfils and the different values and interests at stake. This article provides a typology of all possible performance criteria from a multi-actor point of view including an overview of the different values and interests at stake and the possible conflicts of interest.